Study on Mass Transports in Evolution of Separation Bubbles Using LCSs and Lobe Dynamics (Communications in Computational Physics, 2019)
The lobe dynamics and mass transport between separation bubble and mainflow in flow over airfoil are studied in detail, using Lagrangian coherent structures(LCSs), in order to understand the nature of evolution of the separation bubble. Forthis problem, the transient flow over NACA0012 airfoil with low Reynolds numberis simulated numerically by characteristic based split (CBS) scheme, in combinationwith dual time stepping. Then, LCSs and lobe dynamics are introduced and developed to investigate the mass transport between separation bubble and main flow, fromviewpoint of nonlinear dynamics. The results show that stable manifolds and unstablemanifolds could be tangled with each other as time evolution, and the lobes are formedperiodically to induce mass transport between main flow and separation bubble, withdynamic behaviors. Moreover, the evolution of the separation bubble depends essentially on the mass transport which is induced by lobes, ensuing energy and momentumtransfers. As the results, it can be drawn that the dynamics of flow separation could bestudied using LCSs and lobe dynamics, and could be controlled feasibly if an appropriate control is applied to the upstream boundary layer with high momentum.
Keywords: Mass transport; separation bubble; Lagrangian coherent structures; lobe dynamics.